Answer:
11
Step-by-step explanation:
Answer:
step 1. you see in the problem x = 6y + 9 substitue the equation for the x variable in the first equation. so it will be 2(6y+9) - 12y = 7
step 2. solve for y. butttt in this case it looks like it can't be solved .
Step-by-step explanation:
option 3. in the steps i provided substituted x for x equals 6y + 9 which leads you to solve y. if you want you can rearrange 2x-12y=7 to solve for y so it would be 7-2x/-12 = 7
First box, third box, fifth and also sixth =D
I believe the answer would be c!